PENERAPAN MODEL PEMBELAJARAN KOOPERTIF TIPENUMBER HEAD TOGETHER (NHT)UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 15 LUBUK MUDA KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Mazlina, Mazlina; Lazim.N, Lazim.N; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT:The research carried out base on the lowly of the result of IPA in grade Vth SDN 15 Lubuk muda which is about 59,75 within minimal completeness criterion stated is 70. Among 20student, there was only 8 students were able to achieve the score of minimal completeness criterion stated. The purpose of this research is to improve student’s achievemet on IPA of the five graders in SDN15 Lubuk mudawith the application of NHT (number Head Together). This research was classroom action research consist of 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After implementation of NHT (number Head Together) model. it was abtained student’s outcomes in UH I within average 63,50(improved from basic score 6,27%). The average score form UH II was 80,00(improved 25,98%). Teachers activities results in the first meeting of the first cycle was 66,66% (good category), and then 75% (good category) for the second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 83,33% (very good category) and then 87,5% (very good category) for second meeting in cycle II. Students activity in the first meeting of the cycle I was 66,66% (good category), 75 (good category) for the second meeting in the cycle I. And then in the first meeting of the second cycle was 79,16% (very good category), 83,33% (very good category) for the second meeting in cycle II. Based on the result it can be concluded that implementation ofNHT (number Head Together). model can IPA in theree graders at SDN 15 Lubuk mudaKecamatan Siak Kecil Kabupaten Bengkalis.Keywords :NHT (Number Head Together).), Students Achievement the Result Of IPA